Formation of single crystalline tellurium supersaturated silicon pn junctions by ion implantation followed by pulsed laser melting - 王熙元 黄永光 刘德伟 朱小宁 崔晓 朱洪亮 (Journal of semiconductors, 2013)
Pn junctions based on single crystalline tellurium supersaturated silicon were formed by ion implantation followed by pulsed laser melting（PLM）.P type silicon wafers were implanted with 245 keV ^126Te^＋ to a dose of 2×10^15 ions/cm^2,after a PLM process（248 nm,laser fluence of 0.30 and 0.35 J/cm^2,1-5 pulses,duration 30 ns）,an n^＋ type single crystalline tellurium supersaturated silicon layer with high carrier density（highest concentration 4.10×10^19 cm^3,three orders of magnitude larger than the solid solution limit） was formed,it shows high broadband optical absorption from 400 to 2500 nm.Current-voltage measurements were performed on these diodes under dark and one standard sun（AM 1.5）,and good rectification characteristics were observed.For present results,the samples with 4-5 pulses PLM are best.